Synergistic interactions of ciprofloxacin and extended-spectrum beta-lactams or aminoglycosides against multiply drug-resistant Pseudomonas maltophilia. - Chow, A W (1988)
The susceptibility of 28 clinical isolates of Pseudomonas maltophilia to 16 antimicrobial agents was determined in vitro by a standard agar dilution method with inoculum sizes of 10(4) and 10(6) CFU. All isolates exhibited multiple drug resistance. Nine isolates were selected for studies of combinations of ciprofloxacin with seven antipseudomonal beta-lactams and three aminoglycosides by a checkerboard agar dilution technique. Synergistic or additive combinations of ciprofloxacin in clinically achievable concentrations were most frequent with mezlocillin (89%), followed by cefoperazone (67%), piperacillin (56%), cefsulodin (56%), and ceftazidime (33%), and were infrequent with aztreonam (11%), the aminoglycosides (0 to 14%), or imipenem (0%). Antagonism was not observed in any combination. These data suggest that combinations of ciprofloxacin with these agents may be useful for some nosocomial multiply drug-resistant P. maltophilia infections.